Multifaceted approach to Endometriosis: A review of clinical challenges, psychological impact, and quality of life - Wręczycki, Mariusz; Muraszewska, Emilia; Muraszewski, Łukasz; Kwitowska, Patrycja; Pyjecka, Małgorzata; Ubysz, Eryk; Król, Agata; Lewandowska, Edyta; Łuczyński, Cezary; Paczkowski, Maciej (Quality in Sport, 2026)
Background: Endometriosis is a chronic, systemic inflammatory condition affecting approximately 10% of women worldwide. Despite its prevalence, it remains characterized by a significant diagnostic delay of 7–10 years and a profound impact on psychological well-being and socio-economic productivity. This review aims to evaluate the shift toward non-invasive diagnostic pathways and the integration of multimodal, patient-centered management strategies. Methods: A comprehensive literature review was conducted, focusing on the latest clinical guidelines (2022–2024) and emerging innovations through 2026. The analysis includes the role of high-resolution imaging (TVUS/MRI), molecular biomarkers (salivary miRNA), and the application of Artificial Intelligence in lesion mapping. Results: Current evidence indicates a definitive paradigm shift from invasive laparoscopy toward a "non-invasive first" diagnostic approach. Innovations in AI-enhanced imaging and phenotype-based classification allow for earlier, more precise interventions. Furthermore, non-pharmacological strategies, particularly Exercise-Induced Hypoalgesia (EIH) and anti-inflammatory nutritional interventions (Low-FODMAP), demonstrate significant efficacy in managing chronic pain and improving Quality of Life (QoL). Conclusions: Addressing the global burden of endometriosis requires a multidisciplinary approach that transcends traditional gynecological boundaries. Transitioning to phenotype-specific diagnostics and holistic care models is essential for the sustainability of healthcare systems and for restoring the quality of life for millions of affected women by 2050.